2019
DOI: 10.2166/wst.2020.040
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization of fish scales biochar and their applications in the removal of anionic indigo carmine dye from aqueous solutions

Abstract: The preparation and applications of Tilapia (Oreochromis niloticus) fish scale biochars (FSB) as an adsorbent in the removal of indigo carmine dye (ICD) from aqueous solutions is described. The biochars were prepared through pyrolysis over a temperature range of 200 °C–800 °C and characterized for surface charge, functional groups, thermal stability, particle size and morphology, elemental composition, crystallinity, and surface area by using pHpzc, Fourier transform infrared (FTIR) spectroscopy, thermo-gravim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
1
21
1
Order By: Relevance
“…This implies that initially, the biosorbent contains a higher number of binding sites for the binding of Pb. In the studies that the range of contact time was wider compared to that of current research, after a lapse of some time, depending on the biosorbent and the solution environment, the number of unoccupied sites decreased and gradually became saturated 5 , 39 , 79 .…”
Section: Discussioncontrasting
confidence: 51%
“…This implies that initially, the biosorbent contains a higher number of binding sites for the binding of Pb. In the studies that the range of contact time was wider compared to that of current research, after a lapse of some time, depending on the biosorbent and the solution environment, the number of unoccupied sites decreased and gradually became saturated 5 , 39 , 79 .…”
Section: Discussioncontrasting
confidence: 51%
“…This implies that initially, the biosorbent contains a higher number of binding sites for the binding of Pb. In the studies that the range of contact time was wider compared to that of current research, after a lapse of some time, depending on the biosorbent and the solution environment, the number of unoccupied sites decreased and gradually became saturated (Ayodele and Adekola 2016; Shahzad et al 2017;Achieng et al 2019).…”
Section: Contact Timementioning
confidence: 57%
“…Further investigation of the elemental analysis results was given in Table 5 which reveals that carbon was present in higher levels than other elements, possibly indicating the dominance of carbon‐containing functional groups 43 in adsorbents used in this study. The content (%) of other elements such as sodium, magnesium, and calcium showed a slight increase in biochar compared to dried fish scale adsorbent, whereas the composition of N and P showed unpredictable trends 10 . The EDS spectra of the adsorbents used in this study are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 89%